2009
DOI: 10.1016/j.avsg.2008.08.031
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Ultrasound Speckle Tracking May Detect Vascular Mechanical Wall Changes in Peripheral Artery Bypass Vein Grafts

Abstract: We report the use of high-resolution, phase-sensitive ultrasound speckle tracking to measure the local vessel-wall strain in two subjects with artery-vein bypass grafts. In addition, we combined this technique with a free-hand pressure equalization procedure to elucidate the non-linear effects of blood pressure on vessel wall compliance. While conventional ultrasound imaging can be used to elucidate the mechanical properties of tissues within the body, it is constrained by comparatively lower resolution and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The newest application of elastography to clinical disease states involves vascular pathology, including assessment of thrombus age and overall vascular compliance (de Korte et al 2000, Biswas et al 2010, Weitzel et al 2009. Rubin et al have shown marked changes in stiffness of common femoral clots as they age (Xie et al 2004).…”
Section: Clinical Resultsmentioning
confidence: 99%
“…The newest application of elastography to clinical disease states involves vascular pathology, including assessment of thrombus age and overall vascular compliance (de Korte et al 2000, Biswas et al 2010, Weitzel et al 2009. Rubin et al have shown marked changes in stiffness of common femoral clots as they age (Xie et al 2004).…”
Section: Clinical Resultsmentioning
confidence: 99%
“…These three parameters have been measured by previous investigators to determine vascular mechanics. 1518 Our purpose was to measure these three parameters to predict AV fistula maturation through semi-automated digital image correlation methods.…”
Section: Overview Of the Softwarementioning
confidence: 99%
“…Previous research has demonstrated the feasibility of measuring vascular elasticity using radiofrequency (RF) data. 15,16 However, clinicians are limited to access the RF data in clinical ultrasound machines. Instead, most clinical ultrasound machines provide the digital imaging and communications in medicine (DICOM) data.…”
Section: Introductionmentioning
confidence: 99%
“…This elasticity‐imaging technique using high‐resolution ultrasound speckle tracking has the potential to give highly reliable and accurate measurements of the physical and mechanical characteristics of a vessel with unprecedented spatial resolution. Recently, this method has been applied to peripheral artery bypass grafts and dialysis fistula imaging (14,15). As vein mechanics may play a role in preoperative assessment for dialysis fistula creation, we sought to evaluate the feasibility of applying this method during dilation of a vein undergoing preoperative ultrasound mapping.…”
Section: Discussionmentioning
confidence: 99%